Review: Modeling of Meniscus of Knee Joint During Soccer Kicking - Mohd Azrul Hisham, Mohd Adib; Mohd Firdaus, Mohd Jaafar; Nur Hazreen, Mohd Hasni (IOP Publishing, 2013)
Knee is a part of the body that located between thigh and shank is one of the most complicated and largest joint in human body. The common injuries that occur are ligaments, meniscus or bone fracture which are internal part of the knee. For soccer games, knee is the most critical part that will easily injure due to the shock from an external impact. Torn meniscus is one of the effects. This study will learn about the effect towards the meniscus within the knee joint during soccer kicking. The method use for this paper is by reviewing 14 journals that discussed about the general view of meniscus and also soccer kicking. The selected topics for this review paper are meniscal function, meniscal movement, meniscal tears and also instep kick. As a finding, statistical state that the most meniscal tears which is 73% occurred in athletes who were soccer players, basketball players or skiers. The torn is frequently happening at the medial side rather than lateral side with a percentage of 70%.